The role of interoception in the mechanism of pain and fatigue in fibromyalgia and myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). (13th April 2021) - Sharp, H.; Themelis, K.; Amato, M.; Barritt, A.; Davies, K.; Harrison, N.; Critchley, H.; Garfinkel, S.; Eccles, J.
Abstract : Introduction: Pain, fatigue and anxiety are common features of fibromyalgia and ME/CFS and significantly impact quality of life. Aetiology is poorly defined but dysfunctional inflammatory, autonomic and interoceptive (sensing of internal bodily signals) processes are implicated. Objectives: To investigate how altered interoception relates to baseline expression of pain, fatigue and anxiety symptoms in fibromyalgia and ME/CFS and in response to an inflammatory challenge. Methods: Sixty-five patients with fibromyalgia and/or ME/CFS diagnosis and 26 matched controls underwent baseline assessment: pressure-pain thresholds and self-report questionnaires assessing pain, fatigue and anxiety severity. Participants received injections of typhoid (inflammatory challenge) or saline (placebo) in a randomised, double-blind, crossover design, before completing heartbeat tracking tasks. Three interoception dimensions were examined: subjective sensibility, objective accuracy and metacognitive awareness. Interoceptive trait prediction error was calculated as discrepancy between accuracy and sensibility. Results: Patients with fibromyalgia and ME/CFS had significantly higher interoceptive sensibility and trait prediction error, despite no differences in interoceptive accuracy. Interoceptive sensibility and trait prediction error correlated with all self-report pain, fatigue and anxiety measures, and with lower pain thresholds. Anxiety mediated the positive-predictive relationships between pain (Visual Analogue Scale and Widespread Pain Index), fatigue impact and interoceptive sensibility. After inflammatory challenge, metacognitive awareness correlated with baseline self-reported symptom measures and lower pain thresholds. Conclusions: This is the first study investigating interoceptive dimensions in patients with fibromyalgia and ME/CFS, which were found to be dysregulated and differentially influenced by inflammatory mechanisms. Interoceptive processes may represent a new potential target for diagnostic and therapeutic investigation in these poorly understood conditions. Disclosure: No significant relationships.